The law if slander and Lie against each other when playing Game Among Us - Gunawan, Prananda Satria; Fatimah, Fatimah; Normalasari, Normalasari; Afif, Muhammad Wildan; Helmi, Rahman; Hafidzi, Anwar (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2023)
ABSTRACT Playing games has become a habit and can even become our hobby. And almost everyone has a cellphone that contains various games. Especially now that there is a digital game or online game called among us. Where there are 15 players (Crewmate) and one or two of them will be the killer (Impostor) and the impostor will disguise himself as a crewmate and make alibis and slander other players. What makes me interested in discussing this is because I want to know the view of Islamic law against slandering each other only through playing games or only through a typing (Chat). The method used in this research is to interview several people who play Among Us and combined with several sources derived from journals found on the internet. From this research, slandering each other in the game Among Us is fine because the intention is not to slander each other but to strategize in the game. Key words; slander, among us. ABSTRAK Bermain game sudah menjadi kebiasaan bahkan bisa menjadi sebuah hobi kita. Dan hampir Setiap orang mempunyai handphone yang isinya macam-macam game. Apalagi sekarang ada Sebuah permainan digital atau game online bernama among us. Yang dimana disana ada 15 Pemain (Crewmate) dan salah satu atau dua diantaranya akan ada yang menjadi pembunuh (Impostor) dan sang impostor ini akan menyamar menjadi crewmate dan membuat alibi-alibi Serta memfitnah pemain yang lain. Yang membuat saya tertarik membahas ini adalah karena Ingin mengetahui pandangan hukum islam terhadap saling memfitnah Hanya lewat bermain game atau hanya lewat sebuah ketikan (Chat). Metode yang di gunakan di penelitian ini adalah dengan mewawancarai beberapa orang yang bermain Among Us tersebut dan dipadukan dengan beberapa sumber yang berasal dari jurnal yang terdapat di internet. Dari penelitian ini saling memfitnah dalam game Among Us itu boleh-boleh saja karena niatnya bukan saling memfitnah tapi strategi dalam permainan. Kata kunci ; memfitnah, among us.